Production and evaluation of biofertilizer for sustainable and green agricultural practices of black pepper - Nabila, Satibi (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Black pepper is famous as king of spices and it has value due to its better pungency and aroma. This black pepper also known as peppercorn and its scientific name is Piper nigrum Leonian (P. nigrum L.). Various diseases attacked this black pepper but most common disease is root rot caused by Phytophthora capsici. Main objective of the study is to implement green agricultural practices to protect and conserve the environment by using land for agricUltural practices in sustainable wa, Bacteria Burkholderia unamae PIO (Bioactiv-SFl) and Enterobacter cloacae PH (Bioactiv-SF2) were used to formed biofertilizers which have been applied to black pepper. Serian has been selected as study sites and data on morphology such as number of leave, diameter of leave, height of plant and length of roots of black pepper were recorded for greenhouse trial while color of leaves, height of tree, number of leaves, fruit production and health condition of the tree for field test. For conclusion, T 4 show the best result compared with T 3.